Cobrança da água como instrumento financeiro: rateio de custo - Oliveira, Ailton Carneiro Martins de (2011)
The objective of this study is to identify the costs involved in managing water resourcesin Ceará, a role of responsibility of the Water Resources Management Company. After identifying these costs, some methods of settlement are discussed, identifying which is best suited to Ceará’s reality. Through cost sharing, we identify the appropriate allocation of these and apply a method of charging for water usage. In this valueare included the costs of operation, management, operation and infrastructure, the latter usually ignored in the methods used to calculate the value of the tariff to be charged. When learning about the infrastructure during this research, we found that there is more than a billion dollars invested in the state of Cearafocused on the management of water resources, not including the costs of thetransposition of São Francisco River. After the cost sharing method, the Average Tariff used by the Consortium Tahal - JP Environment was applied to calculate the Average Tariff by Industry in each section. As a result, we have that the tariff charged is currently below the rate needed to cover operation costs, administration, maintenance and infrastructure.